Un élément fini de poutre fissurée: Application à la dynamique des arbres tournants - Arem, Saber El; Maitournam, Habibou (European Journal of Computational Mechanics, 2007)
In this paper, an original method for construction of a cracked beam finite element is presented. The additional flexibility due to the cracks is identified from three-dimensional finite element calculations taking into account the unilateral contact conditions between the cracks lips. Based on this flexibility which is distributed over the entire length of the element, a new cracked finite element stiffness matrix is deduced. Considerable gain in computing efforts is reached compared to the nodal representation of the cracked section when dealing with the numerical integration of differential equations in structural dynamics.